Dissecting the Immune Response to MF59-adjuvanted and Nonadjuvanted Seasonal Influenza Vaccines in Children Less Than Three Years of Age. Issue 1 (January 2015) - Zedda, Luisanna; Forleo-Neto, Eduardo; Vertruyen, André; Raes, Marc; Marchant, Arnaud; Jansen, Wim; Clouting, Heather; Arora, Ashwani; Beatty, Mark E.; Galli, Grazia; Del Giudice, Giuseppe; Castellino, Flora
<x xml:space="preserve">Abstract</x> Introduction: Annual seasonal influenza epidemics are particularly dangerous for the very young, the elderly and chronically ill individuals, in whom infection can cause severe morbidity, hospitalization and death. Existing, nonadjuvanted influenza vaccines exhibit a suboptimal immunogenicity and efficacy in immunologically naive subjects such as young children. Methods: This phase II, randomized clinical trial was conducted to evaluate the antibody and cell-mediated responses to a trivalent influenza vaccine administered without adjuvant (TIV) or adjuvanted with MF59 (ATIV) in previously nonvaccinated children less than 3 years of age. Results: The MF59-adjuvanted vaccine was well tolerated, and induced higher titers of hemagglutination inhibition antibodies able to recognize strains different from the one used in the vaccine (heterovariant) than TIV. The presence of the adjuvant MF59 induced a larger expansion of vaccine-specific CD4+ T cells. Interestingly, the adjuvant MF59 did not modify the cytokine profile of the elicited T cells, characterized by the production of IL-2 and TNF-α, and did not bias the response toward either Th1 or Th2. The advantage of ATIV over TIV was more pronounced for the virus strains that had not circulated in the years that preceded this study and for the heterovariant strains. Conclusion: These data highlight the relevant role played by the oil-in-water adjuvant MF59 in enhancing the immunogenicity of inactivated influenza vaccines in immunologically naive individuals.